Recurring Outbreaks of Lassa Fever in Nigeria: Understanding the Root Causes and Strategies for the Future - Bashar Haruna Gulumbe; Uzairu Aminu; Usman Umar Liman; Abdulrakib Abdulrahim; Zaharaddin Muhammad Kalgo (Sudan Journal of Medical Sciences, 2023)
Abstract Lassa fever is a severe public health problem in Nigeria with far-reaching political, social, cultural, and religious ramifications. Thus, a further understanding of the disease is critical. Despite attempts to end the viral epidemic, the illness has persisted, leading to several major outbreaks in decades. Additionally, the country's epidemic in 2019–2020 set a new global record for the number of Lassa fever cases. This year, 244 cases and 37 deaths had been reported as of January 2023. To identify gaps and provide recommendations for the complete eradication of Lassa fever in the country. This paper investigates the underlying causes of the continuous outbreaks of the illness in Nigeria and the measures to prevent it. The frequent outbreaks of Lassa fever in Nigeria have been linked to several factors, including inadequate waste management, poor sanitation, restricted access to healthcare, and abject poverty. The reoccurring outbreaks are also attributed to a lack of political will, funding, poor coordination and communication, and low public awareness of the illness and its prevention. To effectively stop outbreaks of Lassa fever in Nigeria, the government and partners must continuously put into practice tried-and-true prevention measures such as improved surveillance to detect outbreaks earlier, increased funding and resources to support effective control measures, better primary healthcare facilities and training for healthcare professionals, heightened community engagement and education to raise awareness, and more effective vector control methods to reduce rodent populations, while looking for innovative approaches and dealing with the underlying social and economic problems contributing to the viral persistence.